1982
DOI: 10.2190/j6w4-v0m0-7u1g-cgxk
|View full text |Cite
|
Sign up to set email alerts
|

A Selected Review of the Literature of Adjustment to Hemodialysis

Abstract: The manner in which dialysis patients respond to the stress of chronic renal failure has been focused on in an active body of research. The general approach to the concept of adjustment is critically reviewed and its implications for research considered. A number of important selected factors are reviewed and conclusions in each of the areas are presented. Specific problems are defined and alternative approaches proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…Quality of life (QoL) in end-stage renal disease (ESRD) patients is threatened by multiple biological and psychosocial stresses and has therefore become a focus of attention in evaluating dialysis [1][2][3]. ESRD patients experience severe disruptions of lifestyle, such as limitations in physical activity and social life, and many will encounter difficulties in coping with their disease and the uncertainty of their future [3,4]. Several studies have reported limited QoL in both haemodialysis [5] and peritoneal dialysis patients [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…Quality of life (QoL) in end-stage renal disease (ESRD) patients is threatened by multiple biological and psychosocial stresses and has therefore become a focus of attention in evaluating dialysis [1][2][3]. ESRD patients experience severe disruptions of lifestyle, such as limitations in physical activity and social life, and many will encounter difficulties in coping with their disease and the uncertainty of their future [3,4]. Several studies have reported limited QoL in both haemodialysis [5] and peritoneal dialysis patients [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we noticed that the type of hospital, public or private, posed no clear influence upon the patient' s personality. Other research suggests the same conclusion (15).…”
Section: Discussionmentioning
confidence: 68%
“…HRQoL was discrupted due to various pressures including lifestyle changes, physical activity, a limited social life and an uncertain future. (Blodgett 1981;Sensky 1993). Other researchers also found that these patients were repeatedly experienced a low level of activity, sexual problems and difficulty in maintaining their jobs (Lok 1996;Merkus et al 1997).…”
Section: Introductionmentioning
confidence: 89%